MicroRNA characterization in equine induced pluripotent stem cells - Moro, Lucía Natalia (2018)
Cell reprogramming has been well described in mouse and human cells. The expression of specific microRNAs has demonstrated to be essential for pluripotent maintenance and cell differentiation, but not much information is available in domestic species. We aim to generate horse iPSCs, characterize them and evaluate the expression of different microRNAs (miR-302a,b,c,d, miR-205, miR-145, miR-9, miR-96, miR-125b and miR-296). Two equine iPSC lines (L2 and L3) were characterized after the reprogramming of equine fibroblasts with the four human Yamanaka‘s factors (OCT-4/SOX-2/c-MYC/KLF4). The pluripotency of both lines was assessed by phosphatase alkaline activity, expression of OCT-4, NANOG and REX1 by RT-PCR, and by immunofluorescence of OCT-4, SOX-2 and c-MYC. In vitro differentiation to embryo bodies (EBs) showed the capacity of the iPSCs to differentiate into ectodermal, endodermal and mesodermal phenotypes. MicroRNA analyses resulted in higher expression of the miR-302 family, miR-9 and miR-96 in L2 and L3 vs. fibroblasts (p<0.05), as previously shown in human pluripotent cells. Moreover, downregulation of miR-145 and miR-205 was observed. After differentiation to EBs, higher expression of miR-96 was observed in the EBs respect to the iPSCs, and also the expression of miR-205 was induced but only in the EB-L2. In addition, in silico alignments of the equine microRNAs with mRNA targets suggested the ability of miR-302 family to regulate cell cycle and epithelial mesenchymal transition genes, miR-9 and miR-96 to regulate neural determinant genes and miR-145 to regulate pluripotent genes, similarly as in humans. In conclusion, we could obtain equine iPSCs, characterize them and determine for the first time the expression level of microRNAs in equine pluripotent cells.